Expression of matrix metalloproteinases 2, 7 and 9 in patients with colorectal cancer - Kostova Elena; Slaninka-Miceska Maja; Labacevski Nikola; Jakovski Krume; Trojachanec Jasmina; Atanasovska Emilija; Janevski Vlado; Jovanovik Rubens; Janevska Vesna (Vojnosanitetski Pregled)
Background/Aim. Matrix metalloproteinases (MMPs) are perceived to play a key role in tumor invasion and metastasis by their capacity to degrade basement membranes and extracellular matrix proteins. The aim of this study was to investigate the expressions of MMP-2, MMP-7 and MMP-9 in tumor tissue and their relation to clinicopathologic features in patients with colorectal cancer. Methods. Specimens of resected colorectal cancer and surrounding normal tissue of 82 patients were immunohistochemically stained for MMP-2, MMP-7 and MMP-9. The results of immunohistochemical expression of MMPs were correlated with some clinical and pathologic parameters. Results. Immunohistochemical expression of MMP-2 was more frequent in the patients with higher preoperative serum levels of carcinoembryonic antigen (CEA) (p = 0.047), MMP-2 (p = 0.018), MMP-9 (p = 0.036) and in those with lymph node metastasis (p = 0.018) and the advanced stage of the disease (p = 0.046). Expression of MMP-7 was more frequent in the patients with elevated preoperative serum levels of: CEA (p = 0.012), MMP-7 (p = 0.036), MMP-9 (p = 0.023) and with deeply invasive neoplasms (p = 0.027). MMP-9 cell expression was in a positive correlation with elevated preoperative serum levels of: CEA (p = 0.013), MMP-2 (p = 0.012), MMP-9 (p = 0.018) and depth of CRC invasion, i.e. Tparameter (p = 0.027). Conclusion. Immunohistochemical expression of MMPs is a useful indicator of the disease development and progression in patients with colorectal cancer.